Structural Changes on the Surface of Alloy Ti6Al7Nb Under Gas Nitriding - Siyahjani, F.; Atar, E.; Cimenoglu, H. (Springer Science and Business Media LLC, 2016)
The structure of titanium alloy Ti6Al7Nb (the surface nitride layer, the intermediate layer and the diffusion layer) is studied after nitriding at 950, 1120 and 1250°C for 12 h at atmospheric nitrogen pressure. The thickness of the nitride and diffusion layers is shown to increase with increase in the nitriding temperature. The growth of the nitride layer is accompanied by segregation of aluminum in the intermediate layer.